Feasibility Analysis of Patin FishBusiness (Pangasius Sutchi) In Sipungguk Village Pond Salo Sub District Regency of Kampar Riau Province - Syafii, Muhammad; Darwis, Darwis; Arief, Hazmi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSRACT This research was conducted in March 2017 located in Sipungguk Village, Salo Sub-district, Kampar District, Riau Province. The objectives to be achieved in this study is to determine the feasibility of fish farming Patin and to determine the level of sensitivity Patin fish farming in ponds. Location determination is done intentionally (purposive). Determination of respondents in this study is fish farmers Patin in Sipungguk Village Salo Sub District Kampar Regency Riau Province amounted to 7 people. Determination technique of respondents in this study using census method, where all members of fish farmers Patin be 7 respondents. This is in accordance with the opinion of Arikunto (2010), if the number of small respondents from 100 people data collection methods used by census. The result of feasibility analysis showthat (1) fish farming business of Desa Sipungguk is financially feasible with positive NPV investment criteria of IDR 711,668,578, BCR 1.37, IRR 65,13% and Payback Period 4 years (2) sensitivity analysis conducted on fish farming business Patin Sipungguk Village is not sensitive to changes in cost increment by 10%, decrease of benefits by 10%, and cost increase and decrease of benefit by 10%.Keywords: Patin Fish, business feasibility, cultivation, financial, sensitivity